The Constraining Dynamics to Promote the Inclusive Village Governance in an Autocratic Leadership Setting - Muhammad Taufiq; Rahmad Hidayat (Universitas Pancasakti, 2022)
This article discusses the implementation dynamics of the Village Law in a certain context which was backgrounded by the village head's autocratic leadership style that tends to hinder the agenda for institutionalising inclusive governance based on social justice in the village development management. Accountability and citizen engagement as the foundation of term inclusive governance are the principal factors that must be implemented by the Village Government in their routine tasks. As qualitative research with a case study approach, this research utilized a purposive sampling technique to determine the key informants targeted from the elements of the government and villagers. To limit the focus of interest, this research only presents a discussion about the implementation dynamics of the Village Law with the setting of the leadership style of the Village Head in the 2011-2017 period. Field findings show that Dorokobo Village, Kempo District, Dompu Regency has complex socio-economic problems, thus requiring the presence of a responsive government and active villagers to jointly manage various development activities. Unfortunately, expectations of ideal leadership are not widely found in the past structure of the Village Government because they were only busy with various administrative activities and absent from substantive matters. Political leaders came with a procedural and even autocratic style so that the regular participation spaces were limited opened by only involving the elite without the presence of all components of the community. The absence of a progressive process to develop institutional accountability was due to the lack of power that can compel the Village Government to apply the principles of accountability and transparency in their activities.